#TITLE_ALTERNATIVE# - NIM : 13014077, MICHAEL
Heavy metals have been widely used in several industries, such as paint industry, battery industry, machine construction, etc. One of the most dangerous heavy metals that might pollute the environment is cadmium. Cadmium is known as a carcinogenic substance that causes cancer if exposed in certain dosage. One of the heavy metals removal method is by adsorbing the heavy metals using biosorbent. In this research, we will conduct an experiment of cadmium removal using microalgae Aphanothece sp. as the biosorbent. Besides of using biosorbent, we also use submerged membrane to enhance the performance of our system, known as SMAHS (submerged membrane adsorption hybrid system). Microalgae is chosen as the biosorbent because of its low cost, high capacity, and high selectivity in adsorbing heavy metals. This adsorption system is hypothesized to be able to solve the adsorption problem either in batch system which has slow heavy metal removal, or in continuous system which has low biosorption capacity caused by the high mass transfer limitation. The objective of this research was to determine model which fit with SMAHS’ experimental data, also to analysys the effect of variable experiment to the capacity and efficiency of biosorption process. The variables of this experiment were initial cadmium concentration, amount of regenerated biosorbent, and the interval of biosorbent changing. The effluent of this system was analyzed using AAS (Atomic Absorption Spectroscopy) to measure the remaining cadmium concentration. Based on this research, the efficiency of cadmium removal by SMAHS could achieve 94,53 – 98,36% with the biosorption capacity ranged from 10,70 – 71,70 mg Cd/gram biosorbent. Biosorption capacity was directly propotional with inlet cadmium concentration and interval of biosorbent changing, while efficiency of biosorption was directly proportional with inlet cadmium concentration and amount of regenerated biosorbent. Besides, the results of this research showed that a mass balance model of CSTR (continued stirred tank reactor) and kinetic model of pseudo second order which were modified for regenerating biosorbent, demonstrated a good fit with the experimental data of cadmium removal in SMAHS.